Crisis Communication Strategies in the Digital Era: A Narrative Review of Contemporary Theories, Models, and Practices - Bagas Prasetio (Pusat Publikasi Nusantara, 2025)
This article presents a review of the narrative literature to analyze and synthesize the evolution of crisis communication management, from fundamental theories to contemporary practice in the digital age. The method used is a narrative literature review that comprehensively reviews academic literature, industry reports, and relevant case studies. The results of the analysis show that the effectiveness of modern crisis communication depends on the strategic integration between diagnostic theories such as Situational Crisis Communication Theory (SCCT) and the tactical repertoire of Image Restoration Theory (IRT). Digital transformation has created a paradox, where organizations have more direct communication channels but less control over the overall narrative, thus demanding transparency, speed, and dialogue. Future trends are leading to symbiotic collaboration between humans and Artificial Intelligence (AI) for predictive analysis and response, as well as increasing complexity in dealing with overlapping crises (polycrises). These findings confirm that crisis communication has shifted from a reactive function to a strategic management competency that is essential for organizational resilience.